The effect of conventional herbicides, used for the control of alien vegetation on microbial communities within freshwater biofilms - Van Wyk, Armand Jacobus (Stellenbosch : Stellenbosch University, 2017)
Thesis (MSc)--Stellenbosch University, 2017.